Biomechanical Effect of Coronal Alignment and Ligament Laxity in Total Knee Arthroplasty: A Simulation Study - Ro, Jaehun; Ro, Du Hyun; Kang, Yeokyung; Han, Hyuk-Soo; Shin, Choongsoo S. (Frontiers in Bioengineering and Biotechnology, 2022)
The purposes of this study were to develop a cruciate-retaining total knee arthroplasty musculoskeletal model, which enabled the adjustment of ligament length and implant alignment, validate the model, and evaluate the effect of varus/valgus alignment adjustment and unbalanced medial/lateral ligament laxity during gait. A cruciate-retaining total knee arthroplasty musculoskeletal model was constructed and validated against the in vivo contact forces. This model was transformed to 2° varus/valgus alignment of femoral or tibial replacement models and 2° medial/lateral laxity models. The contact forces and ligament tensions of the adjusted models were calculated. The contact forces in the model showed good agreement with the in vivo contact forces. Valgus replacement alignment with balanced ligament models showed lower contact force at medial compartment than the neutral alignment model, whereas the varus replacement alignment with balanced ligament models showed greater contact force at medial compartment and medial/posterior cruciate ligament tension. The medial laxity with neutral alignment model showed similar contact force with decreased medial ligament tension compared to the balanced neutral alignment model, whereas the lateral laxity with neutral alignment model showed greater contact forces and decreased lateral ligament tension. The cruciate-retaining total knee arthroplasty model was validated using in vivo contact forces. (r = 0.939) Two degrees of valgus alignment adjustment with balanced ligament or neutral alignment with 2° of medial laxity can be safe without increasing contact force or ligament tension compared to neutral alignment with a balanced extension gap. However, 2° of varus alignment adjustment with balanced ligament or neutral alignment with 2° of lateral laxity may be unfavorable due to overloading of the joints and knee ligaments.